Analysis of Learning Styles of Students in Class of XI Science 1 and XI Science 2 at SMAN 3 North Luwu - Jesi Jecsen Pongkendek; Dewi Satria Ahmar (Yayasan Ahmar Cendekia Indonesia, 2020)
The study was a descriptive study with the aim of knowing the description of the learning styles of students of Class of XI Science 1 and XI Science 2 of SMAN 3 North Luwu. Description of learning styles that will be obtained in the form of visual style, auditory, and kinesthetic. The subjects of this study were students of class of XI Science 1 totaling 29 students and XI Science 2 totaling 30 students. Retrieval of research data is done by using a student learning style questionnaire. Through descriptive data analysis process results obtained show that (a) the tendency of learning styles of the class of XI Science 1 student: 18 students as visual (62.1%), 4 students as auditory (13.8%), and 7 students as kinesthetic ( 24.1 %%); (b) the tendency of students' learning styles in class of XI Science 2: visual are 15 students (50%), auditory are 9 students (30%), and kinesthetic are 6 students (20%). Through this research, it can be seen that the learning styles of students are different, some tend to be visual, auditory, or kinesthetic. Although it appears that the tendency of learning styles of students in Class of XI Science 1 and XI Science 2 is a visual style. Thus, the teacher can determine the right learning design to be implemented in the classroom.